2006
DOI: 10.1111/j.1365-2133.2006.07266.x
|View full text |Cite
|
Sign up to set email alerts
|

Autologous full-thickness skin substitute for healing chronic wounds

Abstract: Application of this novel skin substitute provides a promising new therapy for healing chronic wounds resistant to conventional therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 29 publications
6
62
0
4
Order By: Relevance
“…ASC may be more suited for use in skin constructs designed for chronic wounds in which activation of the inert wound bed is essential for healing. 30 This is in line with others who showed that ulcers treated with ASC in rats showed increased capillary density and granulation tissue thickness. 46 In contrast, dermal fibroblasts may be more suited for use in skin constructs designed for the treatment of deep burns where overactivation of the wound bed and stimulation of excessive granulation tissue needs to be avoided in order to reduce the chance of hypertrophic scar formation.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…ASC may be more suited for use in skin constructs designed for chronic wounds in which activation of the inert wound bed is essential for healing. 30 This is in line with others who showed that ulcers treated with ASC in rats showed increased capillary density and granulation tissue thickness. 46 In contrast, dermal fibroblasts may be more suited for use in skin constructs designed for the treatment of deep burns where overactivation of the wound bed and stimulation of excessive granulation tissue needs to be avoided in order to reduce the chance of hypertrophic scar formation.…”
supporting
confidence: 90%
“…30 Keratinocytes (5 · 10 5 cells/SS) were seeded on top of acellular human dermis (prepared from glycerol-preserved donor skin [Euro Skin Bank, Beverwijk, The Netherlands]) and cultured, submerged, in keratinocyte medium. ASC and dermal fibroblasts were cultured in 0.4 mm pore size transwells (Cat.…”
Section: Cell Isolation and Culturementioning
confidence: 99%
“…Using fibroblasts to treat chronic and acute ulcers relieves the pain, accelerates the healing process with fewer scars, and from another viewpoint, improves cosmetic results (13). After application of cutaneous equivalents on surgical acute ulcers, their effect on the stimulating granular tissues was confirmed and the transplanted tissue was not rejected (14). The results of the current study recommended the application of fibroblasts as an effective therapeutic modality to treat recalcitrant DFUs.…”
Section: Discussionmentioning
confidence: 59%
“…One milliliter of the culture medium was poured into each well of the CES including cellular suspension and the CES without cellular suspension as a control were put on. The CESs were incubated at 37°C in 5% of CO 2 , with fresh medium changes evon tissue engineering and the clinical applications have already been reported as the most advanced therapy (11,27,28). The development of the scaffold which is mainly made from collagen may promote the expansion of tissue engineering methods and may make a contribution to perform clinical application in regenerative medicine near future.…”
Section: -D Culture Of Fibroblasts In Cesmentioning
confidence: 99%